Pertanggungjawaban Pidana Pelaku Tindak Pidana Penganiayaan yang Mengakibatkan Kematian - Muhammad Raflenchyo; Eddy Rifai; Dona Raisa M (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Persecution is one of the violent crimes committed against the human body in various forms of action, resulting in injury or pain to a person's body and even death. The act of mistreatment committed by a person, whether intentionally or unintentionally, must be ascertained in advance to determine the snares of sanctions that will be punished for that person. In the Criminal Code, Article 345 provides a qualification formulation that the group of persecution is severe. The inhibiting factors for the role of investigators in criminal acts of persecution that result in death are community factors because people should understand that community life requires the existence of law, not only as a parameter for justice, order, peace and order, but also to ensure legal certainty. The active role of the community will greatly support the success of the investigation process because the more active the support from the community, the more optimal law enforcement will be. Law enforcement officers are expected in implementing law enforcement to prioritize preventive efforts, to disseminate information about the dangers of violent crimes, persecution or other criminal acts that often occur among teenagers. Judges in examining, adjudicating and passing decisions on criminal cases of abuse committed by teenagers or children together, must really have an argument on the best legal considerations.